Transmission of Pulmonary Tuberculosis in Families and Efforts Government Reduces Pulmonary TB Cases in West Sumatra Region - R.Firwandri Marza; Abd Gafar; Syahrum; Aini Yusra (Miracle Journal Get Press, 2024)
Classified as dangerous and emergency in the world. This disease is a serious concern in Indonesia, with the second highest number of cases in the world. In this study, we aim to look at efforts to prevent pulmonary TB transmission in families through backing family. Research method based on the concept of observational analytical research with cross-sectional study techniques to describe and examine what factors are related to the incidence of TB transmission in families or households. Result. The results of the analysis showed that there was a significant relationship between the incident and preventive measures, with a p value of 0.046. Based on the results of the analysis, those who were highly knowledgeable (10%), had a 75% risk of developing pulmonary tuberculosis. The results of this study show that family members who lack knowledge about the prevention of pulmonary tuberculosis and who are at risk of pulmonary TB transmission have a high risk of transmission. The implementation of the pulmonary TB transmission prevention program needs to be maximized by the local authorities comprehensively so that the reduction in pulmonary TB can be achieved quickly.